Review article : The Possible Application of Natural Ingredients in Cosmetics for Hair Growth and Strengthening - Budiati, Anarisa; Fit Indri Intan Utami (Journal of Natural Product for Degenerative Diseases, 2025)
Hair is the most significant aspect in supporting look, it requires regular care for problematic scalp and hair, which can be achieved by using products containing hair and scalp care chemicals. The use of natural ingredients as main raw materials and additional raw materials has long been carried out in the cosmetics industry, because they are known to be rich in nutritional content and benefits so they can be used to make beauty and hair care products. The main objective of this literature study activity is to identify the potential contained in the natural to use strengthening and regrowing on the scalp and hair. The literature study was carried out by searching national and international journal literature from 1981 to 2023 regarding natural ingredients in products, namely: lavender, peppermint, rosemary, grapeseed oil, olive oil and bidara oil. Based on literature studies, the results showed that the natural ingredients contained in the product have been proven to have the potential to regrowing, moisturize, strengthen and nourish the scalp and hair, as well as being more environmentally friendly than chemicals and safe to use.